(untitled) (CIPEEX, 2025)
Abdominal aortic aneurysm (AAA) is a condition that is usually asymptomatic and potentially fatal, affecting 4.3% to 8% of men over 60 years old. It is defined as dilation of the aorta greater than or equal to 3.0 cm. There are two main surgical treatment modalities for AAA: open surgery (OS) and endovascular aneurysm repair (EVAR). OS is the traditional approach, but it is more invasive and associated with greater morbidity and longer recovery. EVAR, in turn, is less invasive, with lower perioperative mortality and faster recovery, although it has been linked to higher long-term reintervention rates. Therefore, it is of great importance to compare these two approaches. The objective of this study was to compare the results of OS and EVAR in patients with abdominal aortic aneurysms. This study is a literature review conducted using the National Library of Medicine (PubMed) and The New England Journal of Medicine (NEJM) databases. The descriptors employed were: “Aortic Aneurysm,” “Endovascular Repair,” and “Open Surgery.” The results showed no statistically significant differences between the two techniques in terms of mortality. The 30-day mortality rate for OS was 5.0%, compared with 4.1% for EVAR. However, EVAR was associated with device-related complications such as endoleaks, endograft migration, occlusion of adjacent arterial branches and graft sealing failure, which require continuous surveillance and often additional interventions to maintain long-term effectiveness. This ongoing monitoring may affect the quality of life of patients treated with EVAR. In contrast, OS, although more invasive, generally does not require such intensive long-term follow-up once initial recovery is achieved. Patient profile also plays a crucial role in treatment choice: younger individuals with longer life expectancy and favorable anatomy may benefit more from OS due to its superior durability and lower reintervention rates, whereas EVAR is generally preferred in older patients or those with severe comorbidities who may not tolerate the stress of a more invasive surgery. In conclusion, both EVAR and OS are effective strategies for the management of AAA, each with distinct benefits and limitations. EVAR offers lower perioperative mortality and fewer short-term complications, making it an ideal option for high-risk surgical patients such as the elderly or those with significant comorbidities. However, it requires long-term surveillance due to a higher incidence of late complications and a greater need for reinterventions. In contrast, OS, although more invasive and associated with slower recovery, provides a more durable solution with lower rates of late complications and reoperations, and is often indicated for younger patients or those with complex aneurysm anatomy. The choice between EVAR and OS should be carefully based on patient profile, aneurysm characteristics, and available resources and expertise. As endovascular technology continues to advance, EVAR is expected to achieve improved long-term outcomes, making it an increasingly competitive alternative to open repair.